THE ROLE OF MODERN TRAINING TECHNOLOGIES IN DEVELOPING FUNCTIONAL READINESS OF ATHLETES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
The rapid development of sports science and digital innovation has significantly transformed the methodology of athletic preparation. Functional readiness, understood as the integrated capacity of physiological, biomechanical, and psychological systems to sustain optimal performance under competitive conditions, has become a central concept in contemporary sports training. The purpose of this study is to analyze the role of modern training technologies in enhancing functional readiness among athletes. The research explores wearable monitoring systems, biomechanical analysis tools, artificial intelligence-based performance modeling, virtual and augmented reality applications, and data-driven load management strategies.The study is based on a systematic analysis of contemporary scientific literature in sports physiology, sports biomechanics, and training theory. The findings demonstrate that modern technologies allow precise monitoring of training loads, early detection of overtraining risks, individualized program design, and optimization of recovery processes. The integration of digital tools contributes to improved cardiovascular endurance, neuromuscular coordination, strength, and psychological resilience.The article concludes that modern training technologies serve not only as supportive tools but also as transformative instruments in sports training systems, significantly increasing the efficiency of functional preparation and long-term athletic development.